Household saving, health, and healthcare utilization in Japan. (24th June 2021) - Alzuabi, Raslan; Brown, Sarah; Gray, Daniel; Harris, Mark N; Spencer, Christopher
Abstract: We explore the effects of health and healthcare utilization on household saving and financial portfolios using data from the Japanese Household Panel Survey and the Keio Household Panel Survey. Poor psychological well-being is found to be associated with lower levels of savings and smaller financial portfolios, whereas associations with poor physical health are largely absent. Significantly, our findings do not support the hypothesis that poorer physical health is associated with savings accumulation. In contrast, healthcare utilization in the form of hospital visits, hospitalization, and health screening is associated with greater savings and larger financial portfolios. This suggests that healthcare-based incentives to accumulate savings and financial wealth are related to channels associated with investment in health.